2018
DOI: 10.3389/fpsyg.2018.00401
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory From the Psychological and Neurosciences Perspectives: A Review

Abstract: Since the concept of working memory was introduced over 50 years ago, different schools of thought have offered different definitions for working memory based on the various cognitive domains that it encompasses. The general consensus regarding working memory supports the idea that working memory is extensively involved in goal-directed behaviors in which information must be retained and manipulated to ensure successful task execution. Before the emergence of other competing models, the concept of working memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
229
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(251 citation statements)
references
References 99 publications
(227 reference statements)
16
229
0
6
Order By: Relevance
“…Results showed that MA led to increased activation of the right precuneus, dorsolateral prefrontal cortex, and angular gyrus regions (Supporting Information, Figure 3), which are consistent with mental arithmetic processing (Fehr et al, 2007;Klein et al, 2013). As challenging mental arithmetic tasks are also known to engage working memory resources (Menon, 2010), the activation of dorsolateral prefrontal cortex is also consistent with the engagement of working memory during the calculation task (Chai, Abd Hamid, & Abdullah, 2018). Together, these findings confirm the task-related effects in MA relative to PF, and suggest that there may be a functional separation between the pPC and aPC subregions in BRO processing under mental arithmetic-based cognitive loading.…”
Section: Task-related Effectssupporting
confidence: 55%
“…Results showed that MA led to increased activation of the right precuneus, dorsolateral prefrontal cortex, and angular gyrus regions (Supporting Information, Figure 3), which are consistent with mental arithmetic processing (Fehr et al, 2007;Klein et al, 2013). As challenging mental arithmetic tasks are also known to engage working memory resources (Menon, 2010), the activation of dorsolateral prefrontal cortex is also consistent with the engagement of working memory during the calculation task (Chai, Abd Hamid, & Abdullah, 2018). Together, these findings confirm the task-related effects in MA relative to PF, and suggest that there may be a functional separation between the pPC and aPC subregions in BRO processing under mental arithmetic-based cognitive loading.…”
Section: Task-related Effectssupporting
confidence: 55%
“…To perform this task, it is not enough to simply keep a representation of recently presented items in short-term memory; the working memory buffer also needs to be updated continuously to keep track of what the current stimulus must be compared to. In other words, the participant needs to both maintain and manipulate information in working memory (Chai, Abd Hamid, & Abdullah, 2018). Our primary interest was in whether we could detect differences in the task performance after any of the active tPBM sessions (c-tPBM and p-tPBM), relative to the performance after a sham (s-tPBM).…”
Section: Cognitive Task (2-back)mentioning
confidence: 99%
“…For example, a previous study reported that the caudate was important for the manipulation of information in working memory (Chai, Abd Hamid, & Abdullah, 2018;Chen et al, 2016). Meanwhile, we also found that volume alterations in the left-putamen and right-thalamus were negatively correlated with the auditory recognition reaction time and with working memory and cognitive flexibility, was observed structural connectivity with attention and memory related brain regions (Starr et al, 2011).…”
Section: Discussionmentioning
confidence: 99%